Cardiovascular disease in SARS‐CoV‐2 infection. Issue 9 (7th September 2021) - Sato, Kei; Sinclair, Jane E; Sadeghirad, Habib; Fraser, John F; Short, Kirsty R; Kulasinghe, Arutha
Abstract: Pre‐existing cardiovascular disease (CVD) increases the morbidity and mortality of COVID‐19 and is strongly associated with poor disease outcomes. However, SARS‐CoV‐2 infection can also trigger de novo acute and chronic cardiovascular disease. Acute cardiac complications include arrhythmia, myocarditis and heart failure, which are significantly associated with higher in‐hospital mortality. The possible mechanisms by which SARS‐CoV‐2 causes this acute cardiac disease include direct damage caused by viral invasion of cardiomyocytes as well as indirect damage through systemic inflammation. The long‐term cardiac complications associated with COVID‐19 are incompletely characterised and thought to include hypertension, arrhythmia, coronary atherosclerosis and heart failure. Although some cardiac‐related symptoms can last over 6 months, the effect of these complications on long‐term patient health remains unclear. The risk factors associated with long‐term cardiovascular disease remain poorly defined. Determining which patients are most at‐risk of long‐term cardiovascular disease is vital so that targeted follow‐up and patient care can be provided. The aim of this review was to summarise the current evidence of the acute and long‐term cardiovascular consequences of SARS‐CoV‐2 infection and the mechanisms by which SARS‐CoV‐2 may cause cardiovascular disease. Abstract : This review summarises the current evidence of the acute and long‐term cardiovascular consequences of SARS‐CoV‐2 infection and the mechanisms by which SARS‐CoV‐2 may cause cardiovascular disease.